Time Is Ripe to Make Interactional Moves: Bringing Evidence From Four Languages Across Modalities - Lepeut, Alysson; Shaw, Emily (Frontiers in Communication, 2022)
Sign language linguistics has largely focused on lexical, phonological, and morpho-syntactic structures of sign languages, leaving the facets of interaction overlooked. One reason underlying the study of smaller units in the initial stages of development of the field was a pressing concern to ground sign languages as linguistic. The interactive domain has been sidestepped in gesture studies, too, where one dominant approach has been rooted in psycholinguistic models arguing for gesture’s tight relationship with speech as part of language. While these approaches to analyzing sign and gesture have been fruitful, they can lead to a view of language as abstracted from its natural habitat: face-to-face interaction. Such an understanding of how language manifests itself – one that takes for granted the conversational exchange - cannot account for the interactional practices deployed by deaf and hearing individuals within and across various ecological niches. This paper reviews linguistic research on spoken and sign languages, their approaches to gesture that have tended to posit a divide between what is linguistic vs. non-linguistic and sign vs. gesture. Rather than opposing the two, this paper argues for seeing the dynamics between gesture and sign as intimately intertwined both intra- and inter-personally. To ground this claim, we bring evidence from four languages: American Sign Language-English and French Belgian Sign Language-French (Belgian variety) across modalities (signed and spoken) to offer a view of language as situated, dynamic and inherently multimodal. Based on corpus analyses of signers’ and speakers’ face-to-face interactional discourses of two communicative actions, viz. palm-up and index pointing, it is exemplified how ASL-LSFB deaf and English-Belgian French hearing language users mobilize their hands and their whole body to continuously contribute to both linguistic meaning and the management of their social actions with addressees. Ultimately, exploring the interactional synergies arising within and across different communicative ecologies enables scholars interested in the fields of gesture and sign language research to gain a better understanding of the social, heterogeneous nature of language, and as to what it means for spoken and sign languages to be embodied languages.